2019
DOI: 10.3892/ol.2019.11051
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and outcome of patients with acute myeloid leukemia based on FLT3‑ITD mutation with or without additional abnormal cytogenetics

Abstract: The FMS-like tyrosine kinase 3-internal tandem duplication (FLT3-ITD) gene mutation is present in ~20% of patients with de novo acute myeloid leukemia (AML). Patients with an FLT3-ITD mutation have a poor prognosis. However, the prognostic function of FLT3-ITD combined with other cytogenetic abnormalities are not clear. In the present study, a retrospective analysis of 103 newly diagnosed patients with AML was performed. The results revealed that the overall survival (OS) and recurrence-free survival (RFS) tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…In our study, 50% of patients had a normal karyotype by conventional cytogenetic analysis at diagnosis. Consistent with other studies, there were no significant differences in the OS or EFS for normal or abnormal karyotypes in patients with FLT3-ITD mutations ( P =0.699) [ 8 , 19 ]. FLT3-ITD mutations coexisting with other specific molecular genetics and cytogenetic alterations have been frequently reported [ 8 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, 50% of patients had a normal karyotype by conventional cytogenetic analysis at diagnosis. Consistent with other studies, there were no significant differences in the OS or EFS for normal or abnormal karyotypes in patients with FLT3-ITD mutations ( P =0.699) [ 8 , 19 ]. FLT3-ITD mutations coexisting with other specific molecular genetics and cytogenetic alterations have been frequently reported [ 8 ].…”
Section: Discussionsupporting
confidence: 89%
“…In vitro studies have reported that FLT3 inhibitors work synergistically with chemotherapy to induce cytotoxicity [ 22 , 23 ]. Selective next generation FLT3 therapies (gliteritinib, crenolanib, quizartinib) have greater specificity for FLT3 and higher potency than multitargeted TKIs (midostaurin and sorafenib), and clinical trials have shown an improvement in OS even in relapsed/refractory patients [ 2 , 19 ]. This is promising because relapse is common in these patients, and relapsed patients usually present with higher FLT3-ITD mutation burdens and have a poorer response to treatment [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FMS-like tyrosine kinase 3 (FLT3) mutation is one of the most common genetic abnormalities in AML patients [7]. Survival analyses indicated that FLT3 mutation was significantly associated with poor OS, RFS and EFS using data provided by Bullinger L et al [14], which was consisted with previous studies [39,40]. Therefore, further investigation is important for better understanding the biological roles of FLT3 mutations in AML.…”
Section: Discussionmentioning
confidence: 88%
“…The relationship between clinical relevance and the FLT3 mutation status of human AML has been discussed in several studies [ 19 , 23 , 39 ]. From a clinical perspective, AML patients with FLT3-ITD mutations have been associated with poor prognoses, increased white blood cell count at diagnosis, and an increased risk of relapse [ 25 , 41 ]. Moreover, WBC count is also the most important prognostic factor in acute promyelocytic leukemia (APL), and there are poorer outcomes for patients presenting with high WBC counts [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%